"A Community of Survivors": A Grounded Theory of Organizational Support for Survivor-Advocates in Domestic Violence Agencies. (November 2021) - Wilson, Joshua M.; Goodman, Lisa A.
Half of today's domestic violence (DV) advocates are survivors of intimate partner violence (IPV) or other forms of abuse. Yet, little is known about the experiences of those who are both survivors and advocates, especially regarding organizational relationships, policies, and culture, and how these factors shape well-being. This grounded theory study of 12 survivor-advocates identified three dimensions of organizational support that contribute survivor-advocates' well-being: acknowledging their trauma-related needs, fostering belonging, and honoring strengths. In each case, these organizational factors contribute to well-being through the mechanism of validating their identities as survivors. Suggestions for organizations to better support survivor-advocates are discussed.